PENGARUH SOFT SKILL DABN HARD SKILL TERHADAP KINERJA KARYAWAN PADA PT. TRAKINDO UTAMA CABANG MANADO - Marcella Soba; Efendy Rasjid (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2020)
Global competition requires companies to improve the performance of their human resouces. Human resources perfomances is largerly determined by the soft skills and hard skills it has. so that demanding humans can work with the profesionals, technological skills, fast, precise, and understand. The Puporse od thus study was to determine the effect if soft skill and hard skill on Employe Performance ant the PT. Trakindo Utama Manado Branch.